Shortest Distribution Route Determination Of Pesticides Product Using Tabu Search Algorithm (Case Study : CV. Buana Artha Mandiri, Sidoarjo, Indonesia) - Yustina Ngatilah; Anasyah Septiara; Caecilia Pujiastuti; Desak Ayu Clara Dewanti (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Distribution is activity of delivering goods or services from producers to consumers. CV. Artha BuanaMandiri is a company engaged in Agricultural Industrial Chemicals. The products produced by CV. Artha Buana Mandiri are pesticides. With a large area distribution, the company's distribution process is still considered to be less optimal because there is no fixed distribution route due to the large number of routes used for the East Java distribution area, causing delays in the distribution process of pesticide products. The purpose of this study is to minimize the distance to obtain the optimal distribution route. Optimal route determination is included in the problem of Traveling Salesman Problem (TSP). One solution to solve TSP problems is to use the Tabu Search Algorithm. Tabu Search is a metaheuristic method based on local search. The process of performance moves from one solution to the next by choosing the best solution. The main purpose of this method is to prevent the search process from re-searching the space of the solution that has been traced. From the calculation it can be seen that the optimal route of the Tabu Search method is better than the company route with an optimum route of 251.3 km.